2021
DOI: 10.3390/genes12081275
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series of Familial ARID1B Variants Illustrating Variable Expression and Suggestions to Update the ACMG Criteria

Abstract: ARID1B is one of the most frequently mutated genes in intellectual disability (~1%). Most variants are readily classified, since they are de novo and are predicted to lead to loss of function, and therefore classified as pathogenic according to the American College of Medical Genetics and Genomics (ACMG) guidelines for the interpretation of sequence variants. However, familial loss-of-function variants can also occur and can be challenging to interpret. Such variants may be pathogenic with variable expression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In 2015 was published what would become the international standard for DNA variants' classification, the ACMG/AMP guidelines [13]. These guidelines were meant to be applied to many different genes and conditions, and since then are being continually discussed and adapted [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…In 2015 was published what would become the international standard for DNA variants' classification, the ACMG/AMP guidelines [13]. These guidelines were meant to be applied to many different genes and conditions, and since then are being continually discussed and adapted [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…In the report by Wang et al (2022), a seemingly unaffected parent was found to have a pathogenic ARID2 change which was passed on to their child; this suggests that there may be additional individuals with ARID2 changes who have few or no symptoms. Van der Sluijs et al (2021) reported ARID1B variants that appeared to be inherited from unaffected or mildly affected parents, further highlighting that this may be the case in other BAFopathy genes. The use of methylation “signatures” is being increasingly utilized to help identify the pathogenicity of certain variants of uncertain significance in BAFopathy genes as well as other genes (Aref‐Eshghi et al, 2020; Haghshenas et al, 2020; Kerkhof et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Human‐independent phenotyping methodologies provide non‐biased syndrome correlation to facilitate the interpretation of DNA sequencing data (Dudding‐Byth et al, 2017 ; Hsieh et al, 2022 ), with a role in classifying ARID1B variants (van der Sluijs et al, 2021 ). Both GestaltMatcher and FaceMatch had ARID1B as the top‐ranked gene in the variants from the genomic output.…”
Section: Discussionmentioning
confidence: 99%
“…Due to ascertainment bias, individuals with a priori diagnosis of ARID1B‐CSS may over‐represent more discernible features (Bogershausen & Wollnik, 2018 ; Santen et al, 2014 ; van der Sluijs et al, 2019 ; Vergano et al, 1993 ). Pathogenic variants may be inherited from a mildly affected parent (Mignot et al, 2016 ; van der Sluijs et al, 2019 , 2021 ). BAF complex disruption is associated with Coffin–Siris and Nicolaides–Baraitser syndromes ( SMARCA2 OMIM #600014; Wolff et al, 2012 ), collectively known as BAFopathies, which include developmental delay, coarse facial features, and phalangeal abnormalities (Aref‐Eshghi et al, 2018 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%